Productive Development Policies in Trinidad and Tobago: A Critical Review - Ramiro Moya; Anne-Marie Mohammed; Sandra Sookram (Inter-American Development Bank (IDB), 2010)
Even as Trinidad and Tobago seeks productive diversification away from the energy sector, the process underlying the countrys productive development policies (PDP) is in a state of transition from state-directed industrial policy to a newer approach with extensive private-public participation. This study explores the main characteristics of four PDPs in Trinidad and Tobago and reviews them following the related literature (e.g., Rodríguez-Clare, 2005a and 2005b, and Melo and Rodríguez-Clare, 2006). The four PDPs are: a) The process towards the Promotion of Clusters; b) the PDPs for the Tourism industry; c) the classical PDPs for Micro, Small and Medium Enterprises and; d) the Free Trade Zone as a policy designed to compensate for the failure of the State.
Keywords: L52; O25; O54; 330; Industrial policy; Productive development policies; Diversification; Caribbean; Trinidad and Tobago